Nuclei position-control and crystal growth-guidance on frozen substrates for high-performance perovskite solar cells. Issue 25 (5th June 2019) - Wang, Gang; Liao, Liping; Niu, Lianbin; Chen, Lijia; Li, Wenjun; Xu, Cunyun; Mbeng, Elisabeth; Yao, Yanqing; Liu, Debei; Song, Qunliang
Abstract : High-efficiency p–i–n perovskite solar cells with 1.14 V V oc by spin-coating perovskite films on frozen substrates. Abstract : Nucleation and crystal growth are key stages for high-quality perovskite films that dominate the performance of perovskite solar cells. However, the position of nuclei in the films and the orientation of the crystal growth have not yet been intendedly controlled during their fabrication. In this study, we developed a method of spin-coating perovskite films on frozen substrates to control the position of the nuclei and the direction of the crystal growth at the same time. In this way, the position of the crystal nuclei and the growth orientation of the perovskite crystals in the perovskite films can be simultaneously controlled. A high-quality perovskite film with grains spanning vertically the entire film thickness has been obtained using this new method. And an efficient inverted planar solar cell (ITO/PEDOT:PSS/CH3 NH3 PbI3 /PC61BM/BCP/Ag) with the highest power conversion efficiency of 17.14% and open-circuit voltage of 1.14 V has been achieved by using this technique.